2019
DOI: 10.1101/522128
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genomic sequence and comparative genomic analysis of cultivated passion fruit(Passiflora edulis L.)

Abstract: Cultivated passion fruit is a fruit tree widely cultivated in southern China, 24 but little is known about its genomics, which seriously restricts the molecular genetics 25 research of passion fruit. In this study, we analyzed the 165.7Mb representative 26 genome sequences. The results showed that the passion fruit genome contained a large 27 number of simple sequence repeats (SSR). Compared to the cassava and peach 28 genomes, the passion fruit genome has 23,053 predicted genes. These genes can be 29 alig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It has been confirmed that several conserved, as well as speciesspecific miRNAs, are very important for plants in different biological processes and hence, profiling miRNAs in a non-model plant is essential to understand the regulation of various biological phenomena. With the recent draft genome sequence available (Wu et al 2019), the current study offers an insight of miRNAs and their respective targets in passion fruit using bioinformatics as well as wet-lab approach for better understanding the physiological processes in this plant. In summary, in this study for the first time, we have generated the miRNA and respective target profile of passion fruit and performed a comparative miRNA expression study between vegetative and reproductive tissues (leaves and fruits) as well as between two different varieties (yellow and purple skins).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been confirmed that several conserved, as well as speciesspecific miRNAs, are very important for plants in different biological processes and hence, profiling miRNAs in a non-model plant is essential to understand the regulation of various biological phenomena. With the recent draft genome sequence available (Wu et al 2019), the current study offers an insight of miRNAs and their respective targets in passion fruit using bioinformatics as well as wet-lab approach for better understanding the physiological processes in this plant. In summary, in this study for the first time, we have generated the miRNA and respective target profile of passion fruit and performed a comparative miRNA expression study between vegetative and reproductive tissues (leaves and fruits) as well as between two different varieties (yellow and purple skins).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In this study, web tool psR-NATarget (http://plant grn.noble .org/psRNA Targe t/?dowha t=Help) was used to identify the potential miRNA targets of passion fruit. Due to unavailability of passion fruit protein database in the psRNATarget web server, target search was conducted against the protein database of Populus trichocarpa, which is considered as the evolutionary closest species of passion fruit (Wu et al 2019). The parameters were adjusted manually, such as maximum expectation value of 3, translation inhibition ranges of 9-11 nt, number of top targets of 10, penalty for G:U pair of 0.5, and number of mismatches allowed in seed region of 1.5.…”
Section: Prediction Of Mirna Targetsmentioning
confidence: 99%